Optimized Production and Characterization of ?-fructofuranosidase from Penicillium brevicompactum - Uma, C; Gomathi, D; Muthulakshmi, C; Ravikumar, G; Gopalakrishnan, V K (Bangladesh Journal of Microbiology, 2012)
The present study is aimed at the optimization of ?-fructofuranosidase from Penicillium brevicompactum using orange fruit peel waste as a substrate in Czapek Dox as basal medium by submerged fermentation (SmF). The optimum pH, temperature and incubation period for enzyme production were 5, 30°C and 4th day respectively. Of the carbon source, sucrose was recorded to be the best carbon source for enzyme production yeast extract was ideal nitrogen source for the ?-fructofuranosidase production. The enzyme was purified to 5.8 fold with recovery of 3.2% by DEAE-column chromatography and the molecular weight was estimated to be 64 KDa by SDS-PAGE. It has a Vmax value of 15.8 U/mg and Km value of 0.23 mg/ml at pH 6. The enzyme activity was found to be stable at 50°C for 30 minutes and it was stimulated by metal ions like Na+ and Ca2+ and inhibited by Zinc. These results highlight the industrial potentials of the substrates as possible raw materials for ?-fructofuranosidase enzyme production from Penicillium brevicompactum DOI: http://dx.doi.org/10.3329/bjm.v28i1.11803 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 13-18